Space and Planetary Imaging using JPEG2000 - Dias, J. (Proc 7th International Workshop on Simulation for European Space Programmes, ESTEC, Noordwijk, The Netherlands, 2002)
The raising demand for Digital content Rights Management (DRM), protection, and security, enables effective on-line access, exchange, and trading of all types of digital media items (ranging from a simple text file to a large space or planetary image) and, at the same time, support global interoperability of customer devices and traded items, which can only be met by a good mix of open architectures and proprietary technologies. In this paper, we present a novel integrated architecture that supports the secure handling of large remote sensing ISO JPEG2000-coded images, obtained from satellite. This effort is within the scope of further developments and new extensions for this standard, namely: - Trans-coding of proprietary digital image formats used in satellite imagery, to the new JPEG2000 format; - Inexpensive network clusters for parallel computing to improve the algorithmic process of coding very large digital images obtained from satellites. - Coding of multi-component and multi-spectral images as well as volumetric images (JP3D); - Exploration of interactive online image satellite catalogs (JPIP); - Secure transmission, and protection of the image content based on OpenSDRM (JPSEC).